Effectiveness of multiple teaching methods in standardized training of internal medicine residents in China: a network meta-analysis - Guan Cheng Ye; Chun Ping Liu; Wei Li; Hua Chao Zhu; Liu Lv; Zhen Hong Zhu; Yong Hong Wang; Jie Hu; Xiao Jia Zheng; Jing Ying Fang; Yu Cao Ma; Ming Xuan Liu; et al. (BMC Medical Education)
Abstract Objective Standardized training for resident physicians in China has been carried out for 10 years, and various new teaching methods have been widely applied in it. The quality of internal medicine teaching is directly related to whether the trainees can master the corresponding clinical skills well and become qualified clinical physicians. The purpose of this study is to systematically evaluate the effectiveness of all teaching methods in Chinese standardized training of internal medicine residents. Methods This study was registered in Inplasy. A comprehensive search of databases, including English and Chinese, was conducted from inception to 30 July 2023. Eligible studies included cohort study and randomized controlled trials (RCT) of all teaching methods in Chinese standardized training of internal medicine residents. A network meta-analysis (NMA) was performed using STATA 16.0. Statistical analysis was done using the mean and standard deviation. The literature quality and risks of bias was assessed using RevMan 5.3. Results A total of 74 articles including 5004 Chinese participants were retrieved, involving 13 interventions, of which 65 were RCT and 9 were cohort studies. This study demonstrated that, in comparison to lecture-based learning (LBL), the integration of problem-based learning (PBL) with WeChat significantly enhanced students' theoretical scores (SMD = 2.3; 95% CI 1.19–3.42; P < 0.05; Sucra = 88%) and decreased the number of dissatisfied students (OR = 0.06; 95% CI 0.01–0.27; P < 0.05; Sucra = 89%). Team-based learning (TBL) was beneficial in improving practical performance (SMD = 2.32; 95% CI 0.74–3.9; P < 0.05; Sucra = 80.1%). Additionally, the PBL combined with clinical practice (PBL + CP) teaching method significantly enhanced students' performance in medical record analysis (SMD = 4.84; 95% CI 3.08–6.59; P < 0.05; Sucra = 99.9%). Furthermore, PBL effectively improved students' self-directed learning abilities (SMD = 1.98; 95% CI 0.05–3.91; P < 0.05; Sucra = 75.8%). Conclusion New teaching methods represented by PBL + Wechat, CBL + Wechat, PBL + CBL are more effective in improving the academic performance of Chinese resident physicians in standardized training compared to control therapy, and have gained more recognition from students.